Investigating a single sensor ability in the characterisation of drinkable water: a pilot study. (14th September 2016) - Santonico, Marco; Parente, Francesca Romana; Grasso, Simone; Zompanti, Alessandro; Ferri, Giuseppe; D'Amico, Arnaldo; Pennazza, Giorgio
Abstract: Physical and chemical characterization of Bottled water is certified on the bottle‐label, which reports the analysis performed by a qualified laboratory. All these data can be suitable treated via multidimensional evaluation and the value of certain parameters against a specific threshold, can address some of these water samples to the treatment of specific medical issues or more in general for dietary options. These thresholds are often referred only to two or three of the listed parameters. In this work, a single voltammetric sensor has been used to characterize 14 different species of bottled water, after a calibration procedure with saline matrices. The sensor has the capability to discriminate among water samples with different dry residue and it is also able to predict the parameters reported on the bottle‐label with an acceptable resolution. Considering the portability of the device and its satisfactory repeatability, the sensor could perform a water quality characterisation, synthesizing bottle‐water characteristic in a reproducible and characteristic profile. The device, when fully integrated and calibrated, can support bottled water monitoring in different steps of the production‐distribution‐utilization chain by means of real‐time measurements.